Is limb autotomy really efficient compared to traditional rearing in soft-shell crab (Scylla olivacea) production? - Yushinta Fujaya; Nita Rukminasari; Nur Alam; Muhammad Rusdi; Hanafiah Fazhan; Khor Waiho (Aquaculture Reports, 2020)
There is currently a global high market demand for soft-shell crabs, which are priced much higher than crabs in hard-shell conditions. In order to harvest crabs in soft-shell conditions, they are reared and collected as soon as they molt, and limb autotomy is commonly used to hasten the molting process. In this study, we compared full limb autotomy (the removal of all the appendages except for the swimming legs), partial limb autotomy (the removal of the walking legs), and traditional rearing methods (control) using immature mud crab (Scylla olivacea) juveniles. The longest and shortest molt cycle duration was observed in the control group and the full limb autotomy group, respectively. The molting percentage was the highest in the full limb autotomy group (females) and in the partial and full limb autotomy groups (males; no significant difference between the groups). The survival rate was unaffected by limb autotomy. Post-molting, the carapace length (CL) and body weight (BW) increments of both sexes, and the carapace width (CW) increment of males were the highest in the control group. The average BW after molting was the highest in the control group, followed by the partial and then the full limb autotomy group. The average total harvest weight, however, was lowest in the control group, while no significant difference was observed between the limb autotomy treatments, owing to their low molting percentage and resulting weight gain per animal. Thus, although limb autotomy (partial or full) significantly shortened the duration of the molt cycle, it may not be as efficient as traditional rearing methods as it resulted in soft-shell crabs of lower aesthetic value (with missing limbs or uneven limb sizes), body size, and weight, all of which are important criteria for determining crab prices.